FINANCEMENT DES COOPERATIVES AGRICOLES MAROCAINES, STRUCTURE ET PERFORMANCE - El Ouafy, Sakina; Ed-Dafali, Slimane (European Scientific Journal, ESJ, 2014)
This article aims identifying investment behavior of a sample of Moroccan agricultural cooperatives, especially from the region of Souss Massa Daraa (SMD). There is, first, to determine the preferences of cooperatives in funding methods, and second, to analyze the financial structure of cooperatives, through financial indicators and leverage. The research examines the impact of this financial structure on economic performance. The empirical study examines a sample of 31 cooperatives, through a survey conducted via a questionnaire, and an accounting and financial data analysis of the sample during the period 2009, 2010 and 2011. Assumptions validity tests are based on a descriptive approach, enhanced by an econometric cross-section model.